Rheology and Stability of Hydrocarbon-Based Gelled Fuels for Airbreathing Applications - Simone Dell’Acqua; Francesco Morando; Stefania Carlotti; Filippo Maggi (Aerospace)
Gelled fuels are rheologically complex, non-Newtonian fluids. They combine the benefits of both liquid and solid states, reducing risks of leakage, spilling, and sloshing during storage while maintaining the ability to be sprayed inside a combustion chamber. Additionally, suspending energetic particles, such as metal powders of aluminum and boron, can significantly enhance their energy density compared to conventional liquid fuels. In this study, several kerosene-based and ethanol-based formulations were experimentally investigated, using both organic and inorganic gelling agents. The compositions were optimized in terms of the gellant amount and manufacturing process. Some of the most promising gellants for kerosene include fatty acids, such as Thixcin® R or THIXATROL® ST, and metallic soaps, such as aluminum stearate and zinc stearate. The effects of various co-solvents were assessed, including ketones (methyl isoamyl ketone, methyl ethyl ketone, and acetone) and alcohols (ethanol and octadecanol). Sugar polymers like hydroxypropyl cellulose were tested as gelling agents for ethanol. A preliminary rheological analysis was conducted to characterize their behavior at rest and under shear stress. Finally, a novel approach was introduced to study the stability of the gels under vibration, which was derived from a realistic mission profile of a ramjet. Finally, the ideal gravimetric specific impulse was evaluated through ideal thermochemical computations. The results showed that promising formulations can be found in both kerosene-based and ethanol-based gels. Such compositions are of interest in practical airbreathing applications as they have demonstrated excellent stability under vibration, ideal combustion properties, and pronounced shear-thinning behavior.